Anti-tumour activity of canine activated T-cells and cytokine-induced killer cells against canine malignant melanoma in vitro - Luiza Cesar Conti; Sonia Capellero; Lisa Piras; Emanuela Morello; Sabina Iurascu; Jessica Erriquez; Laura Marconato; Luca Aresu; Raffaella De Maria (The Veterinary Journal, 2026)

Exploring the prognostic implications of programmed death-ligand 1 expression in canine nodal lymphoma: Insights from surface membrane expression, transcript amount and plasmatic levels - Alessandra Ubiali; Luiza Cesar Conti; Raffaella De Maria; Paola Emanuela Maria Dall'Ara; Laura Marconato; Roberta Ferrari; Damiano Stefanello; Maria Amati; Luca Aresu; Fulvio Riondato; Valeria Martini (Research in Veterinary Science, 2026)

Associations between per- and polyfluoroalkyl substances and semen parameters: An updated systematic review and meta-analysis - Andrea Di Nisio; José Francisco López-Gil; Damiano Pizzol; Lucille Ridgell; Dong Keon Yon; Julia Gawronska; Angelica Stellato; Burak Onal; Luca De Toni; Masoud Rahmati; Roshan Ravidran; Lenka Conti; et al. (Journal of Hazardous Materials, 2026)

Serum concentrations of selenium, selenium species and metals in children newly diagnosed with leukemia: a hospital-based case-control study - Marco Vinceti; Teresa Urbano; Bernhard Michalke; Lauren A. Wise; Maria Caterina Putti; Eloise Pulvirenti; Claudia Favara; Silvia Di Federico; Federico Zagnoli; Giorgia Adani; Annadiletta Donà; Roberta Patti; et al. (Environmental Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Prenatal exposure to fine particulate matter PM2.5 and small for gestational age: a Bayesian model for area-based data in Milan - Simone Colombara; Rossella Murtas; Sara Tunesi; Alessandra Guglielmi; Antonio Giampiero Russo; Paola Angelini; Serena Broccoli; Marco Monti; Nicola Caranci; Katia Raffaelli; Daniela Fortuna; Paolo Giorgi Rossi; et al. (Environmental and Ecological Statistics, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

On the role of bacterial gut microbiota from supralittoral amphipod Talitrus saltator (Montagu, 1808) in bioplastic degradation - Alessandro Russo; Aldo D'Alessandro; Monica Di Paola; Benedetta Cerasuolo; Sonia Renzi; Niccolò Meriggi; Luca Conti; Jessica Costa; Rebecca Pogni; Tania Martellini; Alessandra Cincinelli; Alberto Ugolini; et al. (Science of The Total Environment, 2025)

Ingestion of chitosan-starch blends: Effect on the survival of supralittoral amphipods - Alberto Ugolini; Alessandro Russo; Jessica Costa; Alessandra Cincinelli; Tania Martellini; Luca Conti; Duccio Cavalieri; Luca Mercatelli; Rebecca Pogni (Science of The Total Environment, 2024)

Best practices, errors, and perspectives of half a century of plant translocation in Italy - Martina D'Agostino; Luigi Cao Pinna; Marta Carboni; Silvia Assini; Gianluigi Bacchetta; Fabrizio Bartolucci; Lisa Brancaleoni; Fabrizio Buldrini; Angelino Carta; Bruno Cerabolini; Roberta Maria Ceriani; Umberto Clementi; et al. (Conservation Biology, 2024)
Conservation translocations are becoming common conservation practice, so there is an increasing need to understand the drivers of plant translocation performance through reviews of cases at global and regional levels. The establishment of the Italian Database of Plant Translocation (IDPlanT) provides the opportunity to review the techniques used in 186 plant translocation cases performed in the last 50 years in the heart of the Mediterranean Biodiversity Hotspot. We described techniques and information available in IDPlanT and used these data to identify drivers of translocation outcomes. We tested the effect of 15 variables on survival of translocated propagules as of the last monitoring date with binomial logistic mixed‐effect models. Eleven variables significantly affected survival of transplants: life form, site protection, material source, number of source populations, propagation methods, propagule life stage, planting methods, habitat suitability assessment, site preparation, aftercare, and costs. The integration of vegetation studies in the selection of suitable planting sites significantly increased the success of translocation efforts. Although posttranslocation watering had a generally positive effect on translocation outcome, other aftercare techniques did not always increase transplant survival. Finally, we found that how funds were spent appeared to be more important than the actual amount spent. Plant translocations in Italy and in the Mediterranean area should account for the complexity of speciation, gene flow, and plant migrations that has led to local adaptations and has important implications for the choice and constitution of source material.

Altitudinal variation of microplastic abundance in lakeshore sediments from Italian lakes - Marco Parolini; Elena Perin; Beatrice De Felice; Stefano Gazzotti; Adriano Palazzi; Luca Conti; Eleonora Conterosito; Emanuela Rosio; Francesco Bruno; Valentina Gianotti; Roberto Cavallo (Environmental Science and Pollution Research, 2024)
Microplastic (MP) contamination represents an issue of global concern for both aquatic and terrestrial ecosystems, but only in recent years, the study of MPs has been focused on freshwaters. Several monitoring surveys have detected the presence of a wide array of MPs differing in size, shape, and polymer composition in rivers and lakes worldwide. Because of their role of sink for plastic particles, the abundance of MPs was investigated in waters, and deep and shoreline sediments from diverse lakes, confirming the ubiquity of this contamination. Although diverse factors, including those concerning anthropogenic activities and physical characteristics of lakes, have been supposed to affect MP abundances, very few studies have directly addressed these links. Thus, the aim of the present study was to explore the levels of MP contamination in mountain and subalpine lakes from Northern Italy. Fourteen lakes dislocated at different altitudes and characterized by dissimilar anthropic pressures were visited. Lakeshore sediments were collected close to the drift line to assess MPs contamination. Our results showed the presence of MPs in lakeshore sediments from all the lakes, with a mean (± standard deviation) expressed as MPs/Kg dry sediment accounting to 14.42 ± 13.31 (range 1.57–61.53), while expressed as MPs/m 2 , it was 176.07 ± 172.83 (range 25.00–666.67). The MP abundance measured for Garda Lake was significantly higher compared to all the other ones ( F 1,13 = 7.344; P < 0.001). The pattern of contamination was dominated by fibers in all the lakes, but they were the main contributors in mountain lakes. These findings showed that the MP abundance varied according to the altitude of the lakes, with higher levels measured in subalpine lakes located at low altitudes and surrounded by populated areas.

Bioplastics on marine sandy shores: Effects on the key species Talitrus saltator (Montagu, 1808) - Tania Martellini; Alessandro Russo; Alessandra Cincinelli; Saul Santini; Cristiana Lofrumento; Matteo Baini; Samuele Ciattini; Luca Conti; Francesca Mostardini; Luca Mercatelli; Alberto Ugolini (Science of The Total Environment, 2023)

Diachronic Observations Reveal Different and Scale-Dependent Response of Sand Dune Plants to Seashore Dynamics - Stefano Chelli; Fabio Conti; Luca Bracchetti (Estuaries and Coasts, 2022)

Deep Learning to Automatically Segment and Analyze Abdominal Aortic Aneurysm from Computed Tomography Angiography - Francesca Brutti; Alice Fantazzini; Alice Finotello; Lucas Omar Müller; Ferdinando Auricchio; Bianca Pane; Giovanni Spinella; Michele Conti (Cardiovascular Engineering and Technology, 2022)

Optical tissue clearing associated with 3D imaging: application in preclinical and clinical studies - Cinzia Brenna; Carolina Simioni; Gabriele Varano; Ilaria Conti; Eva Costanzi; Mattia Melloni; Luca Maria Neri (Histochemistry and Cell Biology, 2022)
Understanding the inner morphology of intact tissues is one of the most competitive challenges in modern biology. Since the beginning of the twentieth century, optical tissue clearing (OTC) has provided solutions for volumetric imaging, allowing the microscopic visualization of thick sections of tissue, organoids, up to whole organs and organisms (for example, mouse or rat). Recently, tissue clearing has also been introduced in clinical settings to achieve a more accurate diagnosis with the support of 3D imaging. This review aims to give an overview of the most recent developments in OTC and 3D imaging and to illustrate their role in the field of medical diagnosis, with a specific focus on clinical applications. Graphical abstract

IDPlanT: the Italian database of plant translocation - Thomas Abeli; Martina D’Agostino; Simone Orsenigo; Fabrizio Bartolucci; Rita Accogli; Giulia Albani Rocchetti; Claudia Alessandrelli; Arianna Amadori; Filippo Amato; Claudia Angiolini; Silvia Assini; Gianluigi Bacchetta; et al. (Plant Biosystems, 2021)

Conservation status of the Italian flora under the 92/43/EEC ‘Habitats’ Directive - Giuseppe Fenu; Consolata Siniscalco; Gianluigi Bacchetta; Donatella Cogoni; Maria Silvia Pinna; Marco Sarigu; Thomas Abeli; Elena Barni; Fabrizio Bartolucci; Daniela Bouvet; Annalena Cogoni; Fabio Conti; et al. (Plant Biosystems, 2021)

Comparison of environmental impacts related to municipal solid waste and construction and demolition waste management and recycling in a Latin American developing city - Navarro Ferronato; Luca Moresco; Gabriela Edith Guisbert Lizarazu; Marcelo Antonio Gorritty Portillo; Fabio Conti; Vincenzo Torretta (Environmental Science and Pollution Research, 2021)

Does the Partial Raw Cane System Present Possibilities to Increase Sugarcane Field Longevity in Clayey Soil? - Lucas Augusto de Assis Moraes; Cristiane De Conti Medina; Thadeu Rodrigues De Melo; Thiago Ometto Zorzenoni; Jaime Higino Dos Santos Junior; João Tavares Filho (Sugar Tech, 2021)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Plant–environment interactions through a functional traits perspective: a review of Italian studies - Stefano Chelli; Michela Marignani; Elena Barni; Alessandro Petraglia; Giacomo Puglielli; Camilla Wellstein; Alicia T. R. Acosta; Rossano Bolpagni; Luca Bragazza; Giandiego Campetella; Alessandro Chiarucci; Luisa Conti; et al. (Plant Biosystems, 2019)

Copper and Zinc in Rhizosphere Soil and Toxicity Potential in White Oats (Avena sativa) Grown in Soil with Long-Term Pig Manure Application - Lucas Benedet; Lessandro De Conti; Cleiton Junior Ribeiro Lazzari; Vilmar Müller Júnior; Deborah Pinheiro Dick; Cledimar Rogério Lourenzi; Paulo Emílio Lovato; Jucinei José Comin; Tadeu Luis Tiecher; Felipe Klein Ricachenevsky; Gustavo Brunetto (Water, Air, & Soil Pollution, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Chemically and size-resolved particulate matter dry deposition on stone and surrogate surfaces inside and outside the low emission zone of Milan: application of a newly developed “Deposition Box” - Luca Ferrero; Marco Casati; Lara Nobili; Luca D’Angelo; Grazia Rovelli; Giorgia Sangiorgi; Cristiana Rizzi; Maria Grazia Perrone; Antonio Sansonetti; Claudia Conti; Ezio Bolzacchini; Elena Bernardi; et al. (Environmental Science and Pollution Research, 2018)

The Ventotene Volcanic Ridge: a newly explored complex in the central Tyrrhenian Sea (Italy) - Marco Cuffaro; Eleonora Martorelli; Alessandro Bosman; Alessia Conti; Sabina Bigi; Filippo Muccini; Luca Cocchi; Marco Ligi; Giovanni Bortoluzzi; Davide Scrocca; Simonepietro Canese; Francesco L. Chiocci; et al. (Bulletin of Volcanology, 2016)

Physiological Changes in Maize Grown in Soil with Copper and Zinc Accumulation Resulting from the Addition of Pig Slurry and Deep Litter over 10 Years - Lucas Benedet; Jucinei José Comin; Rosete Pescador; Paulo Armando Victoria de Oliveira; Paulo Belli Filho; Lessandro De Conti; Rafael da Rosa Couto; Paulo Emílio Lovato; Stefano Cesco; Tanja Mimmo; Gustavo Brunetto (Water, Air, & Soil Pollution, 2016)

Persistence with pharmacological treatment in the specialist mental healthcare of patients with severe mental disorders - Valentino Conti; Antonio Lora; Andrea Cipriani; Ida Fortino; Luca Merlino; Corrado Barbui (European Journal of Clinical Pharmacology, 2012)

Aortic Valve Repair via Neo-Chordae Technique: Mechanistic Insight Through Numerical Modelling - Emiliano Votta; Luca Paroni; Carlo A. Conti; Alessandra Pelosi; Andrea Mangini; Paolo D’Alesio; Riccardo Vismara; Carlo Antona; Alberto Redaelli (Annals of Biomedical Engineering, 2012)

Measles-induced respiratory distress, air-leak and ARDS - M. Piastra; R. Onesimo; D. Luca; L. Lancella; L. Marzano; G. Rosa; D. Pietrini; P. Valentini; G. Conti (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Restricted indications for the use of antibiotics in acute otitis media - Federico Marchetti; Luca Ronfani; Sergio Conti Nibali; Maurizio Bonati; Giorgio Tamburlini (European Journal of Clinical Pharmacology, 2004)